Potency of the novel PolC DNA polymerase inhibitor CRS0540 in a disseminated Listeria monocytogenes intracellular hollow-fibre model - Patel, Swati; Chapagain, Moti; Mason, Clifford; Gingrich, Matthew; Athale, Shruti; Ribble, Wendy; Hoang, Teresa; Day, Joshua; Sun, Xicheng; Jarvis, Thale; Ochsner, Urs A; Howe, David; et al. (Journal of antimicrobial chemotherapy, 2022)
Abstract Background Listeriosis is an orphan disease, which is nevertheless fatal in immunocompromised people. CRS0540 is a novel PolC DNA polymerase inhibitor that has demonstrated good in vitro and in vivo activity against Listeria monocytogenes. Methods Rodent-to-human allometry projection-based human population pharmacokinetics of CRS0540 were used for all studies. CRS0540 pharmacokinetics/pharmacodynamics studies in an intracellular hollow-fibre system model of disseminated listeriosis (HFS-Lister) examined the effect of eight treatment doses, administered daily over 7 days, in duplicate units. Total bacterial burden versus AUC/MIC exposures on each day were modelled using the inhibitory sigmoid Emax model, while CRS0540-resistant bacterial burden was modelled using a quadratic function. Ten thousand-subject Monte Carlo simulations were used to predict an optimal clinical dose for treatment. Results The mean CRS0540 intracellular/extracellular AUC0–24 ratio was 34.07 (standard error: 15.70) as measured in the HFS-Lister. CRS0540 demonstrated exposure-dependent bactericidal activity in the HFS-Lister, with the highest exposure killing approximately 5.0 log10 cfu/mL. The free drug AUC0–24/MIC associated with 80% of maximal kill (EC80) was 36.4. Resistance emergence versus AUC/MIC was described by a quadratic function, with resistance amplification at an AUC/MIC of 54.8 and resistance suppression at an AUC/MIC of 119. Monte Carlo simulations demonstrated that for the EC80 target, IV CRS0540 doses of 100 mg/kg achieved PTAs of >90% at MICs up to 1.0 mg/L. Conclusions CRS0540 is a promising orphan drug candidate for listeriosis. Future PK/PD studies comparing it with penicillin, the standard of care, could lead to this drug as a new treatment in immunocompromised patients.